SOSIALISASI TERKAIT PENCEGAHAN TINDAKAN BULLYING DI SEKOLAH DASAR NEGERI 1 CIJUREY KABUPATEN SUKABUMI - Alfian Ashshidqi Poppyariyana; Annisa Dwi Wahyuni; Dyna Nur Shuhupy; Ristawati Putri; Kiki Aulia Salaswati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Behavior improvement in children is very dependent on the family and the surrounding environment, within the family scope has an important role in teaching something to children and is followed by environmental factors that can affect children's behavior, one of which can affect children in a bad environment, namely bullying. Bullying is an attitude that wants to subdue someone verbally or violently. With the possibility that bullying will occur in children, to prevent the occurrence of bullying, the 27 Thematic Community Service Program students at the Muhammadiyah Sukabumi University conducted a socialization to prevent bullying in elementary school children, which generally prevents it from happening in all elementary schools and in particular prevents bullying in elementary schools. 1 Cijurey, Sukabumi Regency. This socialization is done because it is one of the programs that must be carried out by the 27 Thematic KKN Group to be able to provide benefits for the targets of the 27 Thematic KKN Group, namely students and students of SDN 1 Cijurey. Thus, this socialization is a way to provide knowledge about the prevention of bullying. Thus the socialization of bullying prevention can create good group cooperation without bringing down other groups, and in this case not only students who play a role but the teacher also provides solutions on how to deal with students who are bullied